2005
DOI: 10.1590/s0100-204x2005000700005
|View full text |Cite
|
Sign up to set email alerts
|

Isozymic variability in a Brazilian collection of annatto (Bixa orellana L.)

Abstract: -The objectives of this work were to optimize the isozyme electrophoresis technique for Bixa orellana, and use isozyme markers for a preliminary survey on the genetic variability in Brazilian annatto germplasm accessions. Collection consisted of seed samples from sixty open pollinated trees, representing two Northern and four Southern geographic provenances. The extraction, electrophoresis, and interpretation of annatto isozymes are described. Three out of the twenty-one identified isozyme loci were polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
4
0
2
Order By: Relevance
“…3) showing that B. orellana is self-compatible. This fact also reinforces the existence of maturing synchrony between stigma and pollen proposed by Almeida and Pinheiro (1992), although we may not discard the protandry presented by Gómez (1980) due to the increased genetic variability presented by Carvalho et al (2005c) for B. orellana populations.…”
Section: Biology Of Reproductionsupporting
confidence: 90%
“…3) showing that B. orellana is self-compatible. This fact also reinforces the existence of maturing synchrony between stigma and pollen proposed by Almeida and Pinheiro (1992), although we may not discard the protandry presented by Gómez (1980) due to the increased genetic variability presented by Carvalho et al (2005c) for B. orellana populations.…”
Section: Biology Of Reproductionsupporting
confidence: 90%
“…This low level of polymorphism (40%) was also obtained by other authors working with Bixa orellana. Carvalho et al (2005) evaluated 60 genotypes annatto maintained in germplasm collections from various regions of Brazil and concluded that only 3 of the 21 isozyme loci were polymorphic (14.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Isozyme markers (Medina et al, 2001;Carvalho et al, 2005) have been used to study the genetic diversity among accessions from Venezuela and Brazil. DNA markers, such as sequence-related amplified polymorphism) (Valdez-Oheda et al, 2010) have also been used to examine the genetic diversity of annatto accessions from Mexico, and an amplified fragment length polymorphism protocol has also been established for this species (Fay et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some of them (e.g. Bixa orellana) are maintained for domestic use in folk medicine and/or in traditional cuisines (Carvalho et al 2005;Shilpi et al 2006), while others such as Cecropia spp. and Jatropha gossypiifolia have mainly medicinal uses (Castro et al 1999;Mariz et al 2006).…”
Section: Discussionmentioning
confidence: 99%